Handbook of energy harvesting power supplies and applications - Spies, Peter; Mateu, Loreto; Pollak, Markus (Pan Standford Publishing Pte.Ltd, 2015)
Describes the fundamentals and principles in the field of energy harvesting. This book provides the necessary theory and information to develop energy harvesting power supplies. It explains the overall system design, and gives quantitative assumptions on environmental energy